Production of red-pink pigment from Salinicoccus sp. as natural coloring agent in high-fat-containing foods - Yu, Qinke; Tangudomkan, Pachara; Prakitchaiwattana, Cheunjit; Huang, Wen-Chen (Food Agricultural Sciences and Technology, 2025)
This study investigated the potential of red-pink pigments produced by Salinicoccus sp. (82-1) strains, isolated from salty fermented foods, as an alternative source of natural food colorants with antioxidant and antimicrobial properties. This research aimed to optimize the cultivation of Salinicoccus sp. in a medium derived from salty fermented food and milk, extract the pigments produced, evaluate their bioactive properties (antioxidant and antimicrobial), and finally apply them to food models with high fat content. The optimal cultivation medium consists of 1% peptone water supplemented with 5% milk. This medium yielded a cell count of 8.8 log CFU/ml in a 3 L bioreactor, corresponding to 28.75 g of wet cells, and it yielded a total of 15.65 g of crude pigments. The extracted pigment exhibited significant free radical scavenging activity (51.98% by the DPPH method) and antimicrobial activity against Escherichia coli and Staphylococcus aureus, with clear zones of 12.5 mm and 15.4 mm, respectively. When applied to food models at a concentration of 6.67%, the pigment provided coloration with no antimicrobial activity similar to commercial synthetic (CS) coloring agents. Furthermore, it effectively inhibited rancidity in the food models by reducing the peroxide value significantly compared to the CS coloring agent. In summary, the pigment derived from Salinicoccus sp. has potential for use as a natural food colorant with added functional benefits, offering an alternative to synthetic colorants while providing antioxidant and antimicrobial properties.